Evaluation of cross-sectional imaging features that aid in the differentiation of benign and malignant splenic lesions - Abrishami, Alireza; Khalili, Nastaran; Kooraki, Soheil; Abrishami, Yalda; Grenacher, Lars; Kauczor, Hans-Ulrich (European journal of radiology, 2021)
Purpose - This study aimed to investigate the role of cross-sectional imaging in differentiating between benign and malignant splenic lesions based on various imaging features. - Methods - Database of imaging reports from January 2015 to December 2017 were searched dedicatedly for "spleen" or "splenic" terms to identify patients with splenic lesions found either on CT or MRI. The study cohort consisted of patients who had available histological reports or had follow-up imaging for a minimum of one year. Patients were categorized into the benign subcohort if they did not have a history of extra-splenic malignancy, and had a splenic lesion(s) falling into one of these categories: benign histopathology on biopsy, stable size and enhancement, or decreased size on follow-up imaging. Those who had malignant histopathology on biopsy were included in the malignant subcohort. Various morphologic features and enhancement patterns of these lesions were carefully reviewed by two radiologists who were blinded to the final histopathologic diagnosis. - Results - We identified 161 patients (54 % males, mean age ± SD = 59.7 ± 15.4) including 124 (77 %) in the benign and 37 (23 %) in the malignant subcohort. Benign lesions were more likely to be cystic (21.7 % vs 2.7 %, p < 0.001), homogenous (59.7 % vs. 29.7 %, p = 0.001) and to demonstrate well-defined borders (69.3 % vs. 29.7 % p= <0.001). Malignant lesions had significantly larger diameter (median size: 15 vs 11 mm, p = 0.03). Restricted diffusion was not seen in any of the benign lesions; however, 50 % of malignant lesions demonstrated restricted diffusion (p = 0.003). Features such as lesion distribution, presence of calcification, splenomegaly and number of lesions were not significantly different between benign and malignant lesions. - Conclusion - Smaller lesion diameter, well-defined border and homogeneity favor benign nature of splenic lesions while restricted diffusion should raise suspicion for malignancy.
Gesehen am 09.04.2021